PERLINDUNGAN HUKUM PENGGUNA UANG DIGITAL RUPIAH DALAM PERJANJIAN JUAL BELI - Fiqri, Muhamad Saikul (Legal Studies Journal, 2024)
This study discusses legal protection for users of Rupiah Digital Money in sale and purchase agreements and the responsibility of Bank Indonesia as regulator of the circulation of Rupiah Digital Money in sale and purchase agreements. This type of research is normative legal research, the approach method used is a statutory approach. The primary data collection technique is data collection that is carried out through the basis of library research and document studies. The results of this study are, first, the Digital Rupiah Money  Development will be directed at efforts to mitigate various risks. Assessment and identification of emerging risks based on the aspects of people, process and technology will be carried out in a measurable manner to produce a design and technology for Rupiah Digital Money that is safe, reliable and robust. Second, the implementation of supervision of payment system operators by Bank Indonesia, among others, refers to the Principles For Financial Market Infrastructures (PFMI) issued by the Bank For International Settlements (BIS).